Gestión de créditos y cobranza y su influencia en la performance empresarial de Computel S.A.C, Huamachuco - año 2015 - Ruiz Rivera, Roger Jhonny (2016)
This thesis has taken place in the Company Computel S.A.C, whose market is the city of Huamachuco, La Libertad, Peru. Its main objective has been to explain how it influences the Credit Management and Collection in Business Performance of that company. In reviewing the problematic reality, it has formulated the research question: How the Credit Management and Collection influences the Business Performance of Computel S.A.C, Huamachuco - Year 2015?. For data collection we have been considered two populations: 200 customers between companies and individuals and 4 workers; of them they have obtained samples of 65 customers and four workers respectively. They have applied the respective surveys and interviews the company administrator. According to the results, and following the scientific method has been carried out the analysis and discussion corresponding coming to demonstrate the validity of the hypothesis: "The Credit Management and Collection influences directly and significantly in Business Performance Computel SAC, Huamachuco - Year 2015" Finally they formulated the conclusions and recommendations. It is concluded that the main weaknesses of Credit Management and Collection are selling arrangements (cash - unbalanced credit), lack of policies and rules written credit risk, operational risk unforeseen and methodology and procedures in the collection process determines. It is recommended to formulate and implement policies and modern practices on Credit Management and Collection through formalizing the requirements and procedures for credit approval , follow the formalities of a collection process , align the timing of sales to credit deadlines payments to suppliers , measure risk against market fluctuations and unforeseen , persuade customers to hire security services and insurance agencies, etc.